2011
DOI: 10.1002/jso.21917
|View full text |Cite
|
Sign up to set email alerts
|

Mass‐forming intrahepatic cholangiocarcinoma with marked enhancement on arterial‐phase computed tomography reflects favorable surgical outcomes

Abstract: MF type ICC with marked enhancement within the tumor on arterial CT scans showed a favorable surgical outcome due to its less invasive histopathologic characteristics in patients with MF type ICC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
68
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 30 publications
8
68
1
Order By: Relevance
“…This hypervascular appearance has been suggested to correlate with highly cellular tumors containing less fibrous components or a more vascular component intermixed with the fibrous tissue, smaller size, and a better prognosis [26,[28][29][30], and is also more prevalent in cholangiocarcinoma that develops in cirrhotic liver [15]. This hypervascular appearance was seen in all of the lesions in our cohort.…”
Section: Discussionsupporting
confidence: 56%
“…This hypervascular appearance has been suggested to correlate with highly cellular tumors containing less fibrous components or a more vascular component intermixed with the fibrous tissue, smaller size, and a better prognosis [26,[28][29][30], and is also more prevalent in cholangiocarcinoma that develops in cirrhotic liver [15]. This hypervascular appearance was seen in all of the lesions in our cohort.…”
Section: Discussionsupporting
confidence: 56%
“…Although IMCC is typically hypovascular, IMCC arising from chronic viral hepatitis and the cirrhotic or pre-cirrhotic liver is more likely to be hypervascular after the malignant transformation of the cholangiocytes [27]. It has been reported that hypervascular versus hypovascular IMCC on arterial phase CT correlates with reduced malignant behaviour and better survival [13][14][15]28]. In a previous study, welldifferentiated tumours were found to have greater enhancement on gadoxetic acid-enhanced MRI than moderately or poorly differentiated IMCCs [16].…”
Section: Discussionmentioning
confidence: 95%
“…There have been a few reports indicating that the imaging findings of IMCC correlate with prognosis [12][13][14][15]. IMCCs with abundant tumour fibrous stroma, defined as "scirrhous type", exhibit a delayed enhancement area on CT, which correlates with poor prognosis [12].…”
Section: Introductionmentioning
confidence: 99%
“…A serum AFP level of >20 ng/mL is reported in approximately 20-25 % of ICC patients, and abnormal levels of AFP are often associated with cirrhosis or chronic hepatitis [47][48][49][50]. Recently, AFP-producing ICC cells were reported and the cancer cells expressed some stem cell markers [51,52].…”
Section: Clinical Characteristics Of Icc With Cirrhosis or Chronic VImentioning
confidence: 99%